Favorable subgingival plaque microbiome shifts are associated with clinical treatment for peri-implant diseases - Davide Bazzani; Vitor Heidrich; Paolo Manghi; Aitor Blanco-Miguez; Francesco Asnicar; Federica Armanini; Sara Cavaliere; Alberto Bertelle; Federico Dell’Acqua; Ester Dellasega; Romina Waldner; Daniela Vicentini; et al. (npj Biofilms and Microbiomes, 2024)
Abstract We performed a longitudinal shotgun metagenomic investigation of the plaque microbiome associated with peri-implant diseases in a cohort of 91 subjects with 320 quality-controlled metagenomes. Through recently improved taxonomic profiling methods, we identified the most discriminative species between healthy and diseased subjects at baseline, evaluated their change over time, and provided evidence that clinical treatment had a positive effect on plaque microbiome composition in patients affected by mucositis and peri-implantitis.